Evaluating the Impact of Socio-Economic Variables on GDP per Capita: A Case Study of Kazakhstan - Berdimurat, N.; Zhadigerova, O.Z.; Turdiyeva, Z.; Amankeldi, A.A.; Jakupova, D.Y. (Karagandy University of the name of academician E.A. Buketov, 2024)
Object: To assess the potential for diversification of socio-economic participation of youth and older people in the development of creative industries of the Republic of Kazakhstan. Methods: The research uses methods of indirect selective sociological survey with the allocation of individual focus groups, graphical interpretation of the answers received and their comparative analysis. Findings: The object of the study were the largest cities of Kazakhstan. Four focus groups were surveyed: youth, the elderly, representatives of creative industries, and government agencies. A set of specialized state support measures has been proposed to enhance the socio-economic potential of young people and the elderly. Conclusions: The degree of involvement of young people and the elderly in production and consumption has an impact on the diversification of creative industries. It was revealed that young people are actively involved in the production and consumption of creative products. The study found that older adults are involved in producing and consuming creative industry products, though their participation in production is notably low. Despite having significant potential and past creative experience, their current involvement is limited. Additional information: Presented in this article the study was carried out within the framework of a project funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant № . AP14871023).
Әлеуметтік-экономикалық айнымалылардың жан басына шаққандағы ЖІӨ-ге әсерін бағалау: Қазақстан мысалында
Оценка влияния социально-экономических переменных на ВВП на душу населения: на примере Казахстана
Keywords: GDP; regression; dependence; social; economic; factors; statistics; econometrics